The role of 6-phosphogluconate dehydrogenase in vascular smooth muscle cell phenotypic switching and angioplasty-induced intimal hyperplasia - Amy L. Lu; Li Yin, PhD; Yitao Huang, BS; Zain Husain Islam; Rohan Kanchetty; Campbell Johnston; Kaijie Zhang, MD; Xiujie Xie, PhD; Ki Ho Park, PhD; Charles E. Chalfant, PhD; Bowen Wang, PhD (JVS - Vascular Science, 2024)
Background: Restenosis poses a significant challenge for individuals afflicted with peripheral artery diseases, often leading to considerable morbidity and necessitating repeated interventions. The primary culprit behind the pathogenesis of restenosis is intimal hyperplasia (IH), in which the hyperproliferative and migratory vascular smooth muscle cell (VSMC) accumulate excessively in the tunica intima. 6-Phosphogluconate dehydrogenase (6PGD), sometimes referred to as PGD, is one of the critical enzymes in pentose phosphate pathway (PPP). In this study, we sought to probe whether 6PGD is aberrantly regulated in IH and contributes to VSMC phenotypic switching. Methods: We used clinical specimens of diseased human coronary arteries with IH lesions and observed robust upregulation of 6PGD at protein level in both the medial and intimal layers in comparison with healthy arterial segments. Results: 6PGD activity and protein expression were profoundly stimulated upon platelet-derived growth factor-induced VSMC phenotypic switching. Using gain-of-function (dCas9-mediated transcriptional activation) and loss-of-function (small interfering RNA-mediated) silencing, we were able to demonstrate the pathogenic role of 6PGD in driving VSMC hyperproliferation, migration, dedifferentiation, and inflammation. Finally, we conducted a rat model of balloon angioplasty in the common carotid artery, with Pluronic hydrogel-assisted perivascular delivery of Physcion, a selective 6PGD inhibitor with poor systemic bioavailability, and observed effective mitigation of IH. Conclusions: We contend that aberrant 6PGD expression and activity—indicative of a metabolic shift toward pentose phosphate pathway—could serve as a new disease-driving mechanism and, hence, an actionable target for the development of effective new therapies for IH and restenosis after endovascular interventions.